First Carpometacarpal Arthroplasty with Ligamentous Reconstruction: A Long-Term Follow-up. (September 2014) - Yaffe, Mark A.; Butler, Bennet; Saucedo, James M.; Nagle, Daniel J.
Background: The purpose of the present study is to evaluate a single surgeon's short, intermediate, and long-term clinical, functional, and radiographic outcomes with a trapeziectomy with flexor carpi radialis (FCR) suspension arthroplasty without tendon interposition (LRSA). Methods: Twenty-one patients underwent 26 FCR suspension arthroplasties without tendon interposition by a single senior surgeon. All patients had Eaton stage III and IV carpometacarpal (CMC) osteoarthritis. The Patient-Rated Wrist and Hand Evaluation (PRWHE) and Quick Disabilities of Arm, Shoulder, and Hand (QuickDASH) were used to evaluate functional outcomes. A comprehensive strength and range of motion evaluation was performed to evaluate clinical outcomes. Plain radiographs at rest and with maximal pinch were performed to evaluate for arthroplasty space subsidence. Results: The LRSA exhibited consistent clinical and functional outcomes throughout postoperative follow-up. As the average patient age and time from surgery increased, range of motion (ROM) and PRWHE scores stayed relatively constant, while lateral tip and tip pinch strength deteriorated with time. The LRSA prevented the proximal migration of the first metacarpal in all but one patient. No patients required revision arthroplasty following LRSA. Conclusions: This study demonstrates the consistent short, intermediate, and long-term clinical, functional, and ***radiographic outcomes following a trapeziectomy with FCR suspension arthroplasty.